Mapping the Digital Transformation of Education in Indonesia from 2012 to early 2025: A Bibliometric Analysis of Scopus-Indexed Publications - Fuadiy, Moch. Rizal; Rozi, M. Asep Fathur; Arafah, Nawal Nur; Kamal, Lahij; Sunoko, Ahmad (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
The digital transformation of education in Indonesia has accelerated significantly, particularly after the COVID-19 pandemic. National initiatives like Merdeka Belajar have emphasized digital integration in teaching and learning, prompting scholarly interest in e-learning, online pedagogy, and technology-enhanced instruction. Despite this growing body of literature, there remains a lack of systematic analysis regarding how this research has evolved, which themes have dominated, and how collaboration networks have developed. This study aims to map the research landscape of digital education in Indonesia by conducting a bibliometric analysis of Scopus-indexed journal articles published between January, 1, 2012 and May, 31, 2025. Using the Biblioshiny interface of the R-based Bibliometrix package, 1,131 articles were analyzed to examine publication trends, thematic patterns, prominent keywords, top contributing authors and institutions, and the evolution of co-authorship networks. The results show a notable increase in publication volume beginning in 2020, coinciding with the national shift to online learning. Key research themes include